Indications for a single-stage exchange arthroplasty for chronic prosthetic joint infection: a systematic review. (January 2019) - Thakrar, R. R.; Horriat, S.; Kayani, B.; Haddad, F. S.
Abstract : Aims: Prosthetic joint infections (PJIs) of the hip and knee are associated with significant morbidity and socioeconomic burden. We undertook a systematic review of the current literature with the aim of proposing criteria for the selection of patients for a single-stage exchange arthroplasty in the management of a PJI. Material and Methods: A comprehensive review of the current literature was performed using the OVID-MEDLINE, EMBASE, and Cochrane Library databases and the search terms: infection and knee arthroplasty OR knee revision OR hip arthroplasty OR hip revision, and one stage OR single stage OR direct exchange. All studies involving fewer than ten patients and follow-up of less than two years in the study group were excluded as also were systematic reviews, surgical techniques, and expert opinions. Results: The initial search revealed 875 potential articles of which 22 fulfilled the inclusion and exclusion criteria. There were 16 case series and six comparative studies; five were prospective and 14 were retrospective. The studies included 962 patients who underwent single stage revision arthroplasty of an infected hip or knee joint. The rate of recurrent infection ranged from 0% to 18%, at a minimum of two years' follow-up. The rate was lower in patients who were selected on the basis of factors relating to the patient and the local soft-tissue and bony conditions. Conclusion: We conclude that single-stage revision is an acceptable form of surgical treatment for the management of a PJI in selected patients. The indications for this approach include the absence of severe immunocompromise and significant soft-tissue or bony compromise and concurrent acute sepsis. We suggest that a two-stage approach should be used in patients with multidrug resistant or atypical organisms such as fungus.